Keep calm, teach on : education responding to a pandemic - Vyortkina, Dina; Collins, Neil; Reagan, Timothy G. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"COVID-19 has had massive social, political, and economic consequences, not least in education. Schools and universities globally closed their doors and sought to provide educational services to students in other, alternative ways. This book is a collection of essays about how different institutions and systems of education around the world have attempted to meet the challenges created by COVID-19. It reports the impact of the pandemic in both developed and developing nations and at all levels of education. The collective responses and lessons learned are analyzed to explain the relative success of different coping strategies"-- Provided by publisher.
Keywords: Educational change.; COVID-19 Pandemic, 2020-2023 -- Influence.; Teaching -- Social aspects.; Education -- Computer-assisted instruction.; Social distancing (Public health) and education.; Educational innovations.; Health & Fitness -- Diseases & Conditions -- Contagious (incl. Pandemics); Health, illness and addiction: social aspects.; Coping with, advice about illness and specific health conditions.; Infectious and contagious diseases.; elektronické knihy; electronic books